2004
DOI: 10.1115/1.1641063
|View full text |Cite
|
Sign up to set email alerts
|

Direct Computational Simulations for Internal Condensing Flows and Results on Attainability/Stability of Steady Solutions, Their Intrinsic Waviness, and Their Noise Sensitivity

Abstract: The paper presents a new two-dimensional computational approach and results for laminar/laminar internal condensing flows. Accurate numerical solutions of the full governing equations are presented for steady and unsteady film condensation flows on a sidewall inside a vertical channel. It is found that exit conditions and noise sensitivity are important. Even for stable steady solutions obtained for nearly incompressible vapor phase flows associated with unconstrained exit conditions, the noise sensitivity to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
123
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 31 publications
(133 citation statements)
references
References 29 publications
9
123
1
Order By: Relevance
“…The numerical scheme used here exploits the rigorous analytical and numerical knowledge that exists (see [19]) for solving a reduced hyperbolic form of the interface tracking equation-this ensures convergence and accuracy of both the amplitude and the phase of the predicted interfacial waves. Due to an algorithm improvement, the convergence, grid independence, and satisfaction of all interface/boundary conditions for the results reported here are better than what were reported in [1,2].…”
Section: Introductioncontrasting
confidence: 59%
See 3 more Smart Citations
“…The numerical scheme used here exploits the rigorous analytical and numerical knowledge that exists (see [19]) for solving a reduced hyperbolic form of the interface tracking equation-this ensures convergence and accuracy of both the amplitude and the phase of the predicted interfacial waves. Due to an algorithm improvement, the convergence, grid independence, and satisfaction of all interface/boundary conditions for the results reported here are better than what were reported in [1,2].…”
Section: Introductioncontrasting
confidence: 59%
“…The in-tube geometry (see Fig. 1a) is considered here while some new and improved results for the horizontal and zero gravity channel flow cases-formulated elsewhere [1,2]-are also presented. The results are important for a qualitative understanding of experiments (see, e.g., [3]) dealing with the behavior of a condenser-section (typically of hydraulic diameters in millimeter or sub-millimeter range).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…They concluded that the elliptical section tube has a clear improvement of the vapor condensation over horizontal cylinder. Recently, the stability of the condensing flows has been discussed numerically and experimentally in several works [23][24][25][26][27]. The effect of the free-stream vapor-striking angle on the condensation over a vertical plate was analyzed by Khaled et al [28].…”
Section: Introductionmentioning
confidence: 99%